Geospatial tool-chains: Planning support systems for organisational teams. (December 2019) - Alva, Pradeep; Janssen, Patrick; Stouffs, Rudi
In practice, most planners do not make significant use of planning support systems. Although extensive research has been conducted, the focus tends to be on supporting individual tasks, and the outcomes are often the development of new stand-alone tools that are difficult to integrate into existing workflows. The knowledge contribution in this article focuses on developing a novel spatial decision support framework focusing on the workflows and tool-chains that span across different teams with varying skill sets and objectives, within an organisation. In the proposed framework, the core decision-making process uses a set of decision parameters that are combined using a weighted decision tree. The framework is evaluated by developing and testing a workflow and GIS tool-chain for a real-world case study of land suitability and mixed-use potentiality analysis.